Phyllanthus emblica polyphenol nanoparticles as well as preparation method and application thereof
The preparation of the polyphenol nanoparticles by high-pressure homogenization method solved the problem of insufficient particle size control and stability in the preparation of snail mucus nanoparticles, achieved nano-level particle size distribution and high dispersion, and improved the absorption and retention performance of drugs.
Patent Information
- Application Number
- CN202411952288.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when preparing nanoparticles based on snail mucus, there are problems such as difficulty in controlling particle size, poor dispersion and insufficient stability, which affects the transdermal absorption and dermal retention properties of the drug.
The high-pressure homogenization method was used to homogenize the extract of the pericypeptide polyphenol with the snail mucus and oil phase to prepare the pericype polyphenol nanoparticles to ensure that their particle size is at the nanometer level, the polydispersion index is less than 0.1, and has good potential stability.
The ulcer polyphenol nanoparticles with uniform particle size, good dispersion and complete structure were successfully prepared, which improved the transdermal absorption and dermal retention performance of the drug, and enhanced its stability and bioavailability in the drug delivery system.
Smart Images

Figure CN119700712A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials, and more specifically, relates to a kind of emblica polyphenol nanoparticles and a preparation method and application thereof. Background Art
[0002] Phyllanthus emblica L, also known as oil orange, has the main chemical components of phenolic acids, tannins, flavonoids, terpenes, sterols, vitamins and volatile oils. Phyllanthus emblica L has the effects of clearing heat and cooling blood, promoting digestion and strengthening the stomach, promoting fluid and relieving cough. It can be used for blood heat and blood stasis, indigestion, dry throat and sore throat, cold and fever, etc. It is known as the "three major fruits" of Tibetan medicine together with Terminalia chebula and Terminalia chebula, and has extremely high medicinal value. Phyllanthus emblica L is widely distributed in Yunnan, Hainan, Guizhou, Sichuan, Guangxi, Guangdong and Fujian in the southwest inland and southern coastal areas of China, and has a long history of medicinal use. In recent years, the World Health Organization of the United Nations has designated it as one of the three health plants to be promoted for cultivation worldwide, and in 1998 it was included in the list of "medicine and food of the same origin". Literature reports that Phyllanthus emblica has three anti-effects, namely anti-tumor, anti-bacterial and anti-inflammatory. Not only that, Phyllanthus emblica also has good effects in protecting the liver, relieving gout and cardiovascular diseases, etc., indicating that Phyllanthus emblica is a drug with research potential.
[0003] According to literature reports, skin can become rough and dry if exposed to ultraviolet radiation B (UVB) for only five minutes; if exposed for a long time, it can also cause skin inflammation, which in turn promotes signs of skin aging such as pigmentation, skin sagging, and loss of moisture and collagen. More seriously, when melanin accumulates to a certain level, it may evolve into melanoma. Therefore, fighting photoaging has become an urgent problem to be solved.
[0004] In the field of pharmaceutical preparations, the introduction of nanotechnology has brought revolutionary changes to drug delivery systems. Nanoformulations can significantly reduce the particle size of drugs, thereby increasing their specific surface area, which is conducive to increasing the solubility of drugs, improving bioavailability, and possibly improving the pharmacokinetic properties of drugs. For transdermal drug delivery systems, it is crucial to ensure that nanoformulations have appropriate nanosize and good dispersibility. These properties can give the preparations good transdermal absorption and dermal retention properties, thereby helping to maximize the efficacy of the drug.
[0005] In the prior art, although a variety of nanoparticle preparation technologies have been developed and applied, they still face some technical difficulties in practical applications. In particular, when preparing nanoparticles based on natural polymer materials, how to ensure the uniformity, stability and biocompatibility of nanoparticles has become an urgent problem to be solved.
[0006] Snail mucus (Helix aspersa muller, HAM) is a natural polymer material that has attracted extensive attention in the field of pharmaceutical preparations and cosmetics in recent years due to its unique physical and chemical properties. Snail mucus is rich in a variety of active ingredients, such as allantoin, glycolic acid, hyaluronic acid and polyphenols, which have multiple properties such as emollient, moisturizing, protective and repairing. However, in the process of preparing nanoparticles using snail mucus, the existing technology has the following major problems: (1) Difficulty in particle size control: Due to the complexity of snail mucus components, it is easy to cause uneven particle size distribution when preparing nanoparticles, resulting in poor dispersion of nanoparticles (PDI>0.1), affecting the transdermal absorption and dermal retention of drugs; (2) Insufficient stability: During the preparation process, the natural polymer structure of snail mucus is easily destroyed, resulting in reduced stability of nanoparticles, which will specifically show results such as larger PDI and / or larger particle size, thereby affecting the long-term storage and use of drugs.
[0007] In response to the above problems, researchers have been seeking improvements and breakthroughs. Although some methods for preparing nanoparticles based on snail mucus have been proposed, these methods are still difficult to completely solve the above technical problems, especially in terms of particle size control and stability.
[0008] Therefore, developing a new method for preparing nanoparticles based on snail mucus can solve the problems existing in the prior art and prepare nanoparticles with nanoparticle size, small PDI (polydispersity index), good stability and biocompatibility, which is of great significance for improving the transdermal absorption and dermal retention of drugs, and promoting the widespread application of nanotechnology in the field of pharmaceutical preparations. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art in preparing nano preparations, such as difficulty in controlling particle size, poor dispersibility and insufficient stability, and to provide a method for preparing emblica polyphenol nanoparticles.
[0010] The purpose of the invention is to provide the emblica polyphenol nanoparticles prepared by the preparation method.
[0011] Another object of the present invention is to provide the application of the Emblica polyphenol nanoparticles.
[0012] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0013] The invention provides a method for preparing emblica polyphenol nanoparticles, comprising the following steps: uniformly mixing a snail mucus aqueous dispersion, an emblica polyphenol extract dispersion and an oil phase, and fully homogenizing the mixture under a pressure of 1200 to 1800 bar to obtain the emblica polyphenol nanoparticles;
[0014] The mass ratio of the snail mucus in the snail mucus aqueous dispersion to the emblica polyphenol extract in the emblica polyphenol extract dispersion is (20-500):1;
[0015] The volume ratio of the solvent in the snail mucus aqueous dispersion to the solvent in the emblica polyphenol extract dispersion is: 1:(0.15-0.25);
[0016] Calculated by volume percentage of the solvent in the snail mucus aqueous dispersion, the volume percentage of the oil phase is 0.01% to 1%.
[0017] Although some methods for preparing nanoparticles based on snail mucus have been proposed, these methods still have some shortcomings, especially in terms of particle size control and stability. The present invention uses a high-pressure homogenization method to prepare emblica polyphenol nanoparticles from emblica polyphenol extract, drug carrier snail mucus and oil phase. The obtained emblica polyphenol nanoparticles successfully reach the nanometer level (<225nm), showing a very small particle size distribution index (PDI <0.1) and good potential stability, indicating that its particle size distribution is extremely uniform and not easy to precipitate; the results of electron microscopy observation show that the emblica polyphenol nanoparticles present a regular spherical structure, there is no adhesion between the particles, and the dispersion is excellent. This observation further verifies the uniformity of the particle size distribution and ensures the stability and effectiveness of the emblica polyphenol nanoparticles in practical applications; in addition, the emblica polyphenol nanoparticles prepared by the present invention also show a high encapsulation rate of more than 30%. This data further proves that the emblica polyphenol nanoparticles have a complete encapsulation structure, which can effectively protect the active ingredient emblica polyphenol extract, while improving its stability and bioavailability in the drug delivery system. In summary, the present invention successfully prepared emblica polyphenol nanoparticles with uniform particle size, good dispersibility and complete structure, providing a new reference for the research and development of drug delivery systems.
[0018] Preferably, the mass ratio of snail mucus in the snail mucus aqueous dispersion to the emblica polyphenol extract in the emblica polyphenol extract dispersion is (50-300):1, further preferably (50-250):1, further more preferably (150-250):1, and most preferably 250:1.
[0019] Preferably, the volume percentage of the oil phase is 0.01% to 0.05% based on the volume percentage of the solvent in the snail mucus aqueous dispersion. Within this range, the obtained emblica polyphenol nanoparticles have a smaller PDI and a smaller particle size.
[0020] Preferably, the volume ratio of the solvent in the snail mucus aqueous dispersion to the solvent in the emblica polyphenol extract dispersion is 1:(0.18-0.22), more preferably 1:0.2. That is, the nanosystem in the present invention mainly uses water as a dispersant.
[0021] Furthermore, the method for preparing the snail mucus aqueous dispersion comprises the following steps: thoroughly mixing the snail mucus with water to obtain the dispersion.
[0022] Furthermore, the preparation method of the emblica polyphenol extract dispersion comprises the following steps: fully mixing the emblica polyphenol extract with an ethanol solution to obtain the dispersion.
[0023] Furthermore, the volume concentration of the ethanol solution is 20% to 80%, preferably 60% to 80%, and more preferably 70%.
[0024] Preferably, the oil phase is selected from one or more of isopropyl linoleate, caprylic / capric triglyceride, ethyl palmitate, and ethyl linoleate. The addition of a small amount of oil phase can further promote the dissolution and dispersion of the emblica polyphenol extract in the system, which is beneficial to reducing the particle size and PDI of the obtained particles.
[0025] Preferably, the mass concentration of the snail mucus aqueous dispersion is 20 to 100 mg / mL, more preferably 80 to 100 mg / mL.
[0026] Preferably, the mass concentration of the emblica polyphenol extract dispersion is 1 to 5 mg / mL, more preferably 1.5 to 3 mg / mL.
[0027] Furthermore, the sufficient homogenization is performed 20 to 40 times, and the time for each homogenization is 1 to 3 minutes, more preferably 2 to 3 minutes.
[0028] Furthermore, the preparation method of the emblica polyphenol extract comprises the following steps:
[0029] S1. Mixing the dried fruit of Phyllanthus emblica and the ethanol solution, heating to boiling for full extraction, concentrating, and drying to obtain a crude extract of Phyllanthus emblica polyphenols;
[0030] S2. The crude extract of emblica polyphenols obtained in step S1 is purified by elution with a macroporous resin, and the eluate is collected, concentrated, and dried to obtain the emblica polyphenol extract.
[0031] Preferably, the type of the macroporous resin is selected from D-101, NKA-9, HPD-100, X-5 or AB-8.
[0032] Preferably, the mass volume ratio of the emblica buds and the ethanol solution is 1: (4-12) g / mL, more preferably 1: (6-10) g / mL, further preferably 1: (7-9) g / mL, and most preferably 1: 8 g / mL.
[0033] Preferably, the volume concentration of the ethanol is 20% to 80%, more preferably 40% to 60%.
[0034] Furthermore, the sufficient extraction time is 30 to 150 min, preferably 60 to 120 min, and more preferably 90 to 110 min.
[0035] Furthermore, in steps S1 to S2, the concentration is to concentrate the extract to remove ethanol using a rotary evaporator; and the drying is freeze-drying.
[0036] Furthermore, the eluent used for the macroporous resin elution purification is an ethanol solution, and the concentration of the ethanol solution is 40% to 80%, preferably 60% to 80%, and more preferably 70%.
[0037] Furthermore, the specific conditions for the macroporous resin elution purification are: loading the sample at a mass concentration of 0.02-0.7 mg / mL (preferably 0.02-0.4 mg / mL), setting a loading flow rate of 1-3 mL / min (preferably 2 mL / min), and setting an elution flow rate of 1-3 mL / min (preferably 2 mL / min).
[0038] The invention protects the emblica polyphenol nanoparticles prepared by the preparation method.
[0039] The present invention also protects the use of the emblica polyphenol nanoparticles in preparing products for resisting skin photoaging.
[0040] The present invention fully proves that the polyphenol extract of Phyllanthus emblica has a significant anti-photoaging effect and can improve light damage, so the product based on the polyphenol extract of Phyllanthus emblica can be used for resisting skin photoaging.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The present invention uses a high-pressure homogenization method and an ultrafiltration centrifugation method to prepare the emblica polyphenol extract, the drug carrier snail mucus and the oil phase into emblica polyphenol nanoparticles. The obtained emblica polyphenol nanoparticles successfully reach the nanometer level, show a very small particle size distribution index (PDI < 0.1) and good potential stability, indicating that the particle size distribution is extremely uniform and not easy to precipitate; the electron microscope observation results show that the emblica polyphenol nanoparticles present a regular spherical structure, there is no adhesion between the particles, and the dispersion is excellent. This observation result further verifies the uniformity of the particle size distribution, ensures the stability and effectiveness of the emblica polyphenol nanoparticles in practical applications; in addition, the emblica polyphenol nanoparticles prepared by the present invention also show a high encapsulation rate of more than 30%. This data further proves that the emblica polyphenol nanoparticles have a complete encapsulation structure, can effectively protect the active ingredient emblica polyphenol extract, and are conducive to improving its stability and bioavailability in the drug delivery system. In summary, the present invention successfully prepared the emblica polyphenol nanoparticles with uniform particle size, good dispersibility and complete structure, which provides a new reference approach for the research and development of drug delivery systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a statistical chart of toxicity experimental data of different concentrations of polyphenol extracts from Emblica officinalis.
[0044] Figure 2 The cell survival rate statistics for different UVB modeling durations; **** indicates P < 0.0001.
[0045] Figure 3 The anti-photoaging efficacy statistical chart of different concentrations of emblica polyphenol extract; among them, * indicates P < 0.05, ** indicates P < 0.01, *** indicates P < 0.001, and **** indicates P < 0.0001.
[0046] Figure 4 The above is a statistical chart of SOD activity detection of different concentrations of polyphenol extracts from Phyllanthus emblica; among them, * indicates P<0.05, ** indicates P<0.01, and *** indicates P<0.001.
[0047] Figure 5 This is the appearance and Tyndall effect diagram of the Phyllanthus emblica polyphenol nanoparticles obtained in Example 3.
[0048] Figure 6 This is a statistical graph of the particle size of the emblica polyphenol nanoparticles obtained in Example 3.
[0049] Figure 7 This is a statistical graph of the Zeta potential of the Emblica polyphenol nanoparticles obtained in Example 3.
[0050] Figure 8This is a statistical graph of the particle size of the emblica polyphenol nanoparticles obtained in Example 8.
[0051] Fig. 9 This is a statistical graph of the particle size of the emblica polyphenol nanoparticles obtained in Example 9.
[0052] Fig.10 This is a statistical graph of the particle size of the emblica polyphenol nanoparticles obtained in Example 10.
[0053] Fig.11 This is a statistical chart of the particle size and PDI of the emblica polyphenol nanoparticles obtained in Comparative Example 5.
[0054] Fig.12 This is a statistical chart of the particle size of the emblica polyphenol nanoparticles obtained in Comparative Example 6.
[0055] Fig.13 This is a statistical chart of the particle size of the emblica polyphenol nanoparticles obtained in Comparative Example 7.
[0056] Fig.14 This is a statistical chart of the particle size of the emblica polyphenol nanoparticles obtained in Comparative Example 8.
[0057] Fig.15 This is the TEM image of the emblica polyphenol nanoparticles obtained in Example 3. DETAILED DESCRIPTION
[0058] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0059] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0060] Phyllanthus emblica, dried mature fruits, were purchased from Shantou City, Guangdong Province.
[0061] Snail mucus was purchased from Guangzhou Yulin Snail Co., Ltd.
[0062] Example 1 Preparation of Phyllanthus emblica polyphenol extract
[0063] 20 g of emblica buddha was weighed, and an ethanol solution with a volume concentration of 56% was added at a volume mass ratio of ethanol to emblica buddha of 8 mL / g. The mixture was reflux-heated until ethanol reached the boiling point and liquid droplets began to drip from the condenser tube, and the time was recorded for 100 minutes, and the temperature was kept constant. The extract was concentrated by a rotary evaporator to remove ethanol to obtain a concentrated solution, which was freeze-dried to obtain a crude emblica buddha polyphenol extract. When used, the powder was added with water to prepare a crude emblica buddha polyphenol solution (0.4 mg / mL), which was purified by D-101 macroporous resin (purification conditions: loading the sample at a mass concentration of 0.4 mg / mL and setting a loading flow rate of 2 mL / min; using 70% ethanol as an eluent and setting an elution flow rate of 2 mL / min), and the collected eluent was concentrated and freeze-dried to obtain the emblica buddha polyphenol extract.
[0064] Example 2 HaCaT cell experiment of polyphenol extract of Phyllanthus emblica
[0065] 1. Experimental methods
[0066] (1) Cultivation of HaCaT cells
[0067] In a cell safety cabinet, use a pipette to remove the culture medium in the culture bottle, and wash off the suspended cells with PBS buffer solution; after adding trypsin digestion, add DMEM complete culture medium to terminate digestion; gently blow the cells attached to the wall, transfer the cells to a centrifuge tube, and centrifuge for 4 minutes (4000r / min). During the centrifugation, wash the culture bottle with PBS buffer solution; after centrifugation, add suitable DMEM complete culture medium to resuspend the cells and transfer them to the culture bottle, and culture them in a 5% CO2, 37°C cell culture incubator.
[0068] (2) Cytotoxicity assay
[0069] 2.1 Experimental Grouping
[0070] Group A: blank (control) group; Group B: experimental group (samples of polyphenol extract of Phyllanthus emblica prepared with DMEM complete medium at 5, 10, 25, 50, 100, 250, 500 μm / mL, as shown in Table 1), each group had 6 replicate wells.
[0071] Table 1 Dosage concentration of Phyllanthus emblica
[0072]
[0073] 2.2 Experimental procedures
[0074] HaCaT cells in the logarithmic growth phase were cultured at 8×10 3The cells were inoculated at a density of 100 / mL in a 96-well plate; after 24 hours, the culture medium was replaced according to the experimental groups; different concentrations of Phyllanthus emblica extract were added, and the culture was continued for 24 hours, then the culture medium was discarded, and 10% CCK-8 solution prepared in DMEM complete culture medium (DMEM diluted, prepared before use) was added to each well, and after incubation for 1 hour, the OD value was detected at 450nm on a microplate reader.
[0075] (3) Establishment of anti-photoaging model
[0076] 3.1 Experimental Grouping
[0077] The cells were divided into seven groups according to the duration, namely 0 (blank control group), 5, 10, 15, 20, 25, and 30 min / group, as shown in Table 2. Each group had 6 replicate wells and the operation was performed in parallel.
[0078] Table 2 Different UVB irradiation durations
[0079]
[0080] 3.2 Experimental procedures
[0081] HaCaT cells in the logarithmic growth phase were cultured at 8×10 3 Cells were inoculated in 96-well plates at a density of 100 cells / mL; UVB modeling was performed when the cell density reached 70%-80%. Before UVB irradiation, the cells were washed twice with PBS buffer solution, and DMEM blank culture medium was added to each well. The 96-well plate was opened and placed under UVB. The blank group was not irradiated with UVB. After modeling, the 96-well plate was placed in a cell culture incubator for culture. After 24 hours of culture, the culture medium was discarded, and 10% CCK8 solution (DMEM diluted, prepared immediately before use) was added. After incubation for 1 hour, the OD value was detected at 450nm on an ELISA reader.
[0082] (4) Pharmacological efficacy of polyphenol extracts from Phyllanthus emblica
[0083] 4.1 Experimental Grouping
[0084] Control group: blank group (DMEM complete medium, no UVB modeling); Model group (DMEM complete medium, UVB modeling); Vc group: control group vitamin C (vitamin C samples prepared with DMEM complete medium at 25 and 50 μm / mL, Vc group); Emblica polyphenol extract group: experimental group (Emblica polyphenol extract samples prepared with DMEM complete medium at 25, 50, 100, and 200 μm / mL, respectively), as shown in Table 3, with 6 replicate wells in each group.
[0085] Table 3 Dosage concentration
[0086]
[0087] HaCaT cells in the logarithmic growth phase were cultured at 8×10 3 The cells were inoculated in a 96-well plate at a density of 100 cells / mL; when the cell density reached 70%-80%, the culture medium in each well was sucked away with a suction pump, and after being rinsed twice with PBS buffer solution, the above concentrations of Phyllanthus emblica extract and positive drug were added, and UVB modeling was immediately started. After modeling, the cells were placed in a cell culture incubator for 24 hours, the culture medium was discarded, 10% CCK8 solution (DMEM diluted, prepared immediately before use) was added, and after incubation for 1 hour, the OD value was detected at 450nm using an ELISA reader.
[0088] (5) SOD kit detection
[0089] HaCaT cells were cultured at 3 × 10 6 The cells were inoculated at a density of 100 / mL in a 6-well plate for overnight culture. The cells were divided into a blank group (control group), a model group (Model group), a drug group (emblica polyphenol extract) and a positive drug group (Vc group). As shown in Table 4, the drug group treated the cells with low, medium and high concentrations of emblica polyphenol extract, and the positive drug group was a vitamin C solution. UVB irradiation was given immediately after drug administration. After the model was successfully established, the 6-well plate was placed in a cell culture incubator for 24 hours of culture, and the supernatant was first discarded, and the cells were subjected to protein extraction, BCA (Bicinchoninic Acid) quantification, and SOD working solution and starting solution were prepared, and SOD detection was performed according to the corresponding kit operating steps.
[0090] Table 4 Dosage concentration
[0091]
[0092] 2. Experimental results
[0093] (1) Results of HaCaT cell toxicity test on polyphenol extracts from Phyllanthus emblica
[0094] The results are as follows Figure 1 As shown, the polyphenol extract of Phyllanthus emblica was not toxic to HaCaT cells at concentrations of 5, 10, 25, 50, and 100 μm / mL. In order to verify whether the drug was dose-dependent, six concentrations of 5, 10, 25, 50, 100, and 250 μm / mL were used for efficacy verification in subsequent UVB modeling and administration.
[0095] (2) Experimental results of establishing the UVB model of HaCaT cells with polyphenol extract of emblica
[0096] Depend on Figure 2It can be seen that through UVB irradiation for 5, 10, 15, 20, 25, and 30 minutes, light damage can be seen at the lowest time of 5 minutes, and the damage becomes more serious with the increase of irradiation time, with significant differences. The present invention selects 15 minutes irradiation time when the cell survival rate is 50% for subsequent cell experiments to verify the efficacy of the polyphenol extract of Phyllanthus emblica.
[0097] (3) Results of the anti-photoaging experiment on HaCaT cells using polyphenol extract from Phyllanthus emblica
[0098] Depend on Figure 3 It can be seen that after UVB modeling, the polyphenol extract of Phyllanthus emblica had significant anti-photoaging effects at concentrations of 25, 50, and 100 μg / mL compared with the Model group, and the effects of 50 and 100 μg / mL were better than those of the positive drug Vc, indicating that it has the effect of improving photodamage at the cellular level.
[0099] (4) Results of the test of polyphenol extract of Phyllanthus emblica L.-SOD kit
[0100] Depend on Figure 4 It can be seen that after SOD detection, it was found that the SOD activity of the Model group was significantly reduced compared with the Control group. Compared with the Model group, the medium and high doses of the drug-treated group could significantly increase the SOD activity, and the effect was better than that of the positive drug, indicating that the drug has excellent antioxidant effect, can protect cells from damage, and has potential in skin protection.
[0101] The above experimental results show that the polyphenol extract of Phyllanthus emblica has a significant anti-photoaging effect and can improve photodamage.
[0102] However, during the processing, storage and use of the polyphenol extract of Phyllanthus amla, its chemical structure will change due to factors such as light, temperature, and pH, thus affecting its stability and biological activity. In addition, the polyphenol extract used directly may have low absorption efficiency in the body due to large particles or complex molecular structure, which limits its bioavailability and effect. Therefore, preparing it into nano-scale, well-dispersed, and highly stable nanoparticles is conducive to fully exerting its original efficacy. Subsequent exploration will explore how to prepare nano-scale, well-dispersed, and stable polyphenol nanoparticles of Phyllanthus amla.
[0103] Example 3 Preparation of Phyllanthus emblica polyphenol nanoparticles
[0104] The high-pressure homogenization method was used to prepare the emblica polyphenol (YGZ-HAM) nanoparticles, which specifically included the following steps: accurately weighing 10 g of snail mucus (HAM), adding 100 mL of deionized water, and stirring in a magnetic stirrer for 10 min to obtain a snail mucus dispersion; weighing 40 mg of emblica polyphenol extract (YGZ), and making up the volume in a 20 mL volumetric flask with 70% ethanol to obtain an emblica polyphenol extract dispersion; then mixing the emblica polyphenol extract dispersion with 10 uL of isopropyl linoleate (the oil phase accounts for 0.01% of the volume percentage of the solvent in the snail mucus dispersion) to obtain a mixed solution, slowly and uniformly adding the obtained mixed solution to the snail mucus dispersion under a magnetic stirring condition of 400 r / min, stirring for 10 min, and then homogenizing 30 times (each homogenization for about 1 minute and 40 seconds) at a pressure of 1500 bar using a high-pressure homogenizer to obtain the emblica polyphenol nanoparticles.
[0105] Examples 4-7 Preparation of Phyllanthus emblica polyphenol nanoparticles
[0106] The difference from Example 3 is that the added amount of snail mucus is 2g (Example 4), 4g (Example 5), 6g (Example 6), and 8g (Example 7), respectively, and the other steps and parameters are the same as those in Example 3.
[0107] Examples 8-10 Preparation of Phyllanthus emblica polyphenol nanoparticles
[0108] The difference from Example 3 is that the amount of oil phase added is 0.1 mL (based on the volume percentage of the solvent in the snail mucus dispersion, the oil phase accounts for 0.1%; Example 8), 0.5 mL (based on the volume percentage of the solvent in the snail mucus dispersion, the oil phase accounts for 0.5%; Example 9), and 1 mL (based on the volume percentage of the solvent in the snail mucus dispersion, the oil phase accounts for 1%; Example 10), and the other steps and parameters are the same as in Example 3.
[0109] Comparative Examples 1 to 5 Preparation of Phyllanthus emblica polyphenol nanoparticles
[0110] The difference from Example 3 is that isopropyl linoleate is not added, and the added amounts of snail mucus are 2 g (Comparative Example 1), 4 g (Comparative Example 2), 6 g (Comparative Example 3), 8 g (Comparative Example 4), and 10 g (Comparative Example 5), respectively. The other steps and parameters are the same as those in Example 3.
[0111] Comparative Examples 6-8 Preparation of Phyllanthus emblica polyphenol nanoparticles
[0112] The difference from Example 3 is that the amount of oil phase added is 1.5 mL (based on the volume percentage of the solvent in the snail mucus dispersion, the oil phase accounts for 1.5%; Comparative Example 6), 2.5 mL (based on the volume percentage of the solvent in the snail mucus dispersion, the oil phase accounts for 2.5%; Comparative Example 7), and 5 mL (based on the volume percentage of the solvent in the snail mucus dispersion, the oil phase accounts for 5%; Comparative Example 8), and the other steps and parameters are the same as in Example 3.
[0113] Experimental Example 1 Determination of embedding rate
[0114] 1. Establishment of encapsulation efficiency methodology
[0115] (1) Investigation of free drug recovery rate: YGZ solutions with different concentrations of 1.00, 2.00, and 3.00 mg / mL were prepared with deionized water and repeated three times. 0.5 mL of YGZ solution was placed in a 1.0×10- 4 , 3.0×10 4 5.0×10 4 The upper layer of the ultrafiltration centrifuge tube was centrifuged at 4000r / min for 30min. The filtrate and the solution before filtration were taken, diluted 1 time with 70% ethanol, filtered through a 0.22μm filter membrane, and determined by HPLC.
[0116] (2) Ultrafiltration recovery rate investigation: The above YGZ solutions of different mass concentrations were added to the blank HAM solution, and then transferred to the MWCO 5.0×10 4 The upper layer of the ultrafiltration tube was repeated three times. The determination was the same as above.
[0117] (3) Determination of encapsulation efficiency: The encapsulation efficiency of YGZ-HAM was determined by ultrafiltration centrifugation. 0.5 mL of YGZ-HAM was placed in a MWCO ultrafiltration tube (relative molecular weight 5.0×10 4 ), centrifuge at 4000r / min for 30min, take the filtrate (C1) and the solution before filtration (C2), dilute 1 times with 70% ethanol, pass through a 0.22μm filter membrane, and determine by HPLC. Substitute the standard curve to calculate the YGZ content, and calculate the encapsulation efficiency of YGZ according to the following formula.
[0118] Encapsulation efficiency = (C2-C1) / C2
[0119] C1 is the amount of drug not encapsulated in YGZ-SM, and C2 is the total amount of drug in YGZ-SM.
[0120] 2. Determination of the embedding efficiency of Phyllanthus emblica polyphenol nanoparticles
[0121] The embedding efficiency of the YGZ-SM nanoparticles obtained in Examples 3 to 7 was determined according to the method of step (3).
[0122] 3. Experimental results
[0123] (1) Experimental results of ultrafiltration tube screening
[0124] Table 5 Free drug recovery results (n = 3)
[0125]
[0126] The results are shown in Table 5. Taking gallic acid, which has the highest content in the polyphenol extract of Phyllanthus emblica, as the indicator, MWCO 1.0×10 4 The average recovery rate of ultrafiltration tube was 81.53%, MWCO 3.0×10 4 The average recovery rate of ultrafiltration tube was 82.23%, MWCO 5.0×10 4 The average recovery rate of ultrafiltration tube was 90.10%, so MWCO 5.0×10 4 The ultrafiltration tube was used for subsequent experiments.
[0127] (2) Experimental results of ultrafiltration recovery rate
[0128] Table 6 Ultrafiltration recovery of different concentrations (n=3)
[0129]
[0130] The results are shown in Table 6. The average ultrafiltration recoveries of low, medium and high mass concentrations were 92%, 91% and 91%, respectively, and the RSDs were 0.42%, 0.70% and 1.36%, respectively, all less than 2%.
[0131] (3) Results of measurement of embedding efficiency of YGZ-SM nanoparticles obtained in Examples 3 to 7
[0132] Table 7 Encapsulation efficiency results of Phyllanthus emblica polyphenol nanoparticles obtained in Examples 3 to 7
[0133]
[0134]
[0135] The results are shown in Table 7. Among the five concentrations, the encapsulation efficiency of the YGZ-SM nanoparticles prepared in Example 3 was better, so the YGZ-SM nanoparticles prepared in Example 3 were used for further exploration.
[0136] (4) Encapsulation efficiency of Phyllanthus emblica polyphenol nanoparticles obtained in Comparative Examples 1 to 5
[0137] Table 8 Encapsulation efficiency results of Phyllanthus emblica polyphenol nanoparticles obtained in Comparative Examples 1 to 5
[0138]
[0139] The results are shown in Table 8. Without adding isopropyl linoleate in the oil phase, no matter how the HAM concentration was adjusted, the encapsulation efficiency of the obtained Phyllanthus emblica polyphenol nanoparticles was low (<15%).
[0140] Experimental Example 2 Tyndall effect and pH determination
[0141] YGZ-HAM nanoparticles were prepared in a 10 mL vial according to the method of Example 3, and their appearance was observed. A laser pen was used to irradiate and observe whether there was Tyndall phenomenon. An appropriate amount of YGZ-HAM nanoparticles was placed in a 10 mL beaker and its pH value was measured using a pH meter.
[0142] The results are as follows Figure 5 As shown, YGZ-HAM nanoparticles are a light yellow uniform liquid. When irradiated with a laser pen, an obvious light path can be observed, which has a Tyndall effect, indicating that the particles of the preparation are nanometer-scale particles; the pH value of YGZ-HAM nanoparticles is 5.42±0.48, which is very suitable for application in certain acidic tissues such as the slightly acidic environment of the skin surface, which helps the nanoparticles to remain stable in these parts and play a better role.
[0143] Experimental Example 3 Determination of Particle Size, Dispersion Coefficient PDI and Potential
[0144] The average particle size, particle size dispersion coefficient and potential of the YGZ-HAM nanoparticles obtained in Example 3 were measured using a particle size analyzer.
[0145] The average particle size and particle size dispersion coefficient of the YGZ-HAM nanoparticles obtained in Examples 8 to 10 and Comparative Examples 5 to 8 were measured using a particle size analyzer.
[0146] The particle size and PDI measurement results of Example 3 are as follows: Figure 6 As shown, the obtained YGZ-HAM nanoparticles were tested by a particle size analyzer, and the average particle size was (130.10±1.81) nm, the polydispersity index PDI was (0.043±0.02), and PDI < 0.1, indicating that the obtained nanoparticles had uniform particle size distribution and excellent dispersibility.
[0147] The potential results of Example 3 are as follows Figure 7 As shown, after the particle size analyzer test, the Zeta potential of the obtained Phyllanthus emblica polyphenol nanoparticles was -41.54±0.42 mV, and the absolute value of the Zeta potential was within 40-60 mV, indicating that the nanoparticles had good stability.
[0148] The particle size and PDI measurement results of Examples 8 to 10 are as follows: Figures 8 to 10 As shown, the average particle sizes of the obtained YGZ-HAM nanoparticles were (195.8±0.5) nm, (221.3±0.2) nm and (197±0.3) nm, all of which were at the nanoscale level, and the PDIs were (0.005±0.010), (0.092±0.036) and (0.078±0.023), respectively, and the PDIs were all <0.1, indicating that the obtained nanoparticles had excellent dispersibility.
[0149] The particle size and PDI results of Comparative Example 5 are as follows: Fig.11 As shown, the average particle size of the obtained YGZ-HAM nanoparticles is (1063±77) nm, and the polydispersity index PDI is (0.536±0.328), that is, the particle size of the YGZ-HAM composite prepared without adding an oil phase is larger, exceeding the nanometer range, and its dispersibility is also poor, PDI>0.1.
[0150] The particle size and PDI measurement results of Comparative Examples 6 to 8 are as follows: Figures 12-14 As shown in the figure, although the average particle size of the obtained YGZ-HAM nanoparticles is in the nanometer range, their polydispersity indexes PDI are (0.130±0.121), (0.155±0.035) and (0.285±0.050), respectively, and PDI is >0.1, indicating that the obtained nanoparticles have poor dispersibility. This also shows that a large amount of oil phase added is not conducive to the preparation of nanoparticles with good dispersibility.
[0151] Experimental Example 4 TEM measurement
[0152] The emblica polyphenol nanoparticles obtained in Example 3 were used as representative nanoparticles to measure their morphology. Specifically, a proper amount of the emblica polyphenol nanoparticles obtained in Example 3 was taken with a pipette and dropped onto a copper grid, and a 2% phosphotungstic acid solution was added for negative staining, and the nanoparticles were allowed to stand for 3 to 5 minutes. After natural drying, the morphological characteristics were observed by TEM at 50 times.
[0153] The results are as follows Fig.15 As shown, after TEM detection with a magnification of 50 times, it can be observed that the YGZ-HAM nanoparticles have a spherical structure, no adhesion phenomenon and uniform dispersion.
[0154] In summary, the YGZ-HAM nanoparticles obtained in the examples show a smaller particle size (<225nm) and an extremely low PDI value (<0.1), which directly reflects its excellent dispersion properties. Low PDI means that the size distribution of the nanoparticles is highly uniform, which is crucial for improving the stability of the drug. In addition, the small size and uniform distribution of the YGZ-HAM nanoparticles enable them to more effectively penetrate biological membranes, such as cell membranes, thereby significantly enhancing the absorption efficiency of the drug. In particular, the representative YGZ-HAM nanoparticles in Example 3 have an absolute potential value of up to 40mV and electron microscopy results without adhesion, which further confirms that the obtained YGZ-HAM nanoparticles have good stability. Therefore, these characteristics of the YGZ-HAM nanoparticles give it significant advantages in drug delivery systems.
[0155] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing emblica polyphenol nanoparticles, characterized in that: The method comprises the following steps: mixing the snail mucus aqueous dispersion, the emblica polyphenol extract dispersion and the oil phase, and fully homogenizing them at a pressure of 1200 to 1800 bar to obtain the emblica polyphenol nanoparticles; The mass ratio of the snail mucus in the snail mucus aqueous dispersion to the emblica polyphenol extract in the emblica polyphenol extract dispersion is (20-500):1; The volume ratio of the solvent in the snail mucus aqueous dispersion to the solvent in the emblica polyphenol extract dispersion is: 1:(0.15-0.25); Calculated by volume percentage of the solvent in the snail mucus aqueous dispersion, the volume percentage of the oil phase is 0.01% to 1%.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the snail mucus in the snail mucus aqueous dispersion to the emblica polyphenol extract in the emblica polyphenol extract dispersion is (50-300):
1.
3. The preparation method according to claim 1, characterized in that: The oil phase is selected from one or more of isopropyl linoleate, caprylic / capric triglyceride, ethyl palmitate, and ethyl linoleate.
4. The preparation method according to claim 1, characterized in that: The mass concentration of the snail mucus aqueous dispersion is 20-100 mg / mL.
5. The preparation method according to claim 1, characterized in that: The mass concentration of the polyphenol extract dispersion of Phyllanthus emblica is 1-5 mg / mL.
6. The preparation method according to claim 1, characterized in that: The preparation method of the emblica polyphenol extract comprises the following steps: S1. Mixing the dried fruit of Phyllanthus emblica and the ethanol solution, heating to boiling for full extraction, concentrating, and drying to obtain a crude extract of Phyllanthus emblica polyphenols; S2. The crude extract of emblica polyphenols obtained in step S1 is purified by elution with a macroporous resin, and the eluate is collected, concentrated, and dried to obtain the emblica polyphenol extract.
7. The preparation method according to claim 6, characterized in that: The type of the macroporous resin is selected from D-101, NKA-9, HPD-100, X-5 or AB-8.
8. The preparation method according to claim 6, characterized in that: The mass volume ratio of the emblica fruit to the ethanol solution is 1: (4-12) g / mL.
9. The emblica polyphenol nanoparticles prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the emblica polyphenol nanoparticles according to claim 9 in the preparation of products for resisting skin photoaging.